Improvement of supply value chains in sustainable small ruminant production systems in Asia - DEVENDRA, C (The Indian Journal of Animal Sciences, 2016)
The paper highlights the importance of meat production from goats and sheep. Goat meat is sought for its high lean meat content, but current production is inadequate, resulting in the highest price in most countries, followed by mutton. Discussions focus on the distribution across agro-ecological zones (AEZs), factors influencing meat production, transportation, types of markets (assembling, distribution markets and weekly markets), characteristics; marketing channels and outlets; buyer preferences for live animals and meats and major market players. Goat skins are core products due to 20 times value addition. Rural markets have numerous advantages and reduce current constraints to marketing. Three factors requiring urgent attention are: (i) economic opportunities to participate in improved marketing systems and value chains, (ii) increased profits and improved livelihoods will benefit the poor, and (iii) potential development of less favoured areas. Strong interdisciplinary R and D and supportive policies can directly enhance socio-economic benefits and reduced poverty among poor farmers and the landless.